Nutritional and therapeutic interventions for diabetes and metabolic syndrome - Bagchi, Debasis, 1954-; Nair, Sreejayan (Academic Press, an imprint of Elsevier, 2018)
Nutritional and Therapeutic Interventions for Diabetes and Metabolic Syndrome, Second Edition, provides an overview of the current diabetes epidemic, outlines the consequences of this crisis, and lays out strategies to forestall and prevent diabetes, obesity and other intricate issues of metabolic syndrome. Contributing experts provide up-to-date global approaches to the critical consequences of metabolic syndrome and make the book an important reference for those working with the treatment, evaluation or public health planning for the effects of metabolic syndrome and diabetes. Completely revised with 15 new chapters, the book includes coverage of the roles of gut microbiome in obesity and diabetes, macrovascular and microvascular complications, diabetes, metabolic syndrome and kidney disease, aspects of diabetic cardiomyopathy, diabetes, Alzheimer's and neurodegenerative diseases, roles of SGLT2 inhibitors in the treatment of type 2 diabetes, novel biomarkers in diabetes, roles of Trigonella foenum-graecumseed extract in type 2 diabetes, beneficial effects of chromium (III) and vanadium supplements in diabetes, prevention of type 1 diabetes, novel drugs in the therapeutic intervention of type 2 diabetes, eHealth and mobile apps for self-management, artificial pancreatic transplantation, non-invasive glucose monitoring, and the app for glucose regulation.